ANALISIS PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL DAN KOMISARIS INDEPENDEN TERHADAP NILAI PERUSAHAAN SEKTOR INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA - sri wahyuti; M. Astri Yulidar Abbas; Gandi Adnan; Elmayani Parembang (Economic Faculty, University of Widya Gama Mahakam Samarinda, 2024)
Analysis of the Influence of Managerial Ownership, Institutional Ownership and Independent Commissioners on the Value of Companies in the Basic Industry and Chemical Sectors Listed on the Indonesia Stock Exchange. This research aims to determine the influence of managerial ownership, institutional ownership and independent commissioners on company value partially and simultaneously. The research method used for this study is comparative with a quantitative approach. The data obtained in this research comes from the financial reports of Basic Industry and Chemical Sector Companies Listed on the Indonesia Stock Exchange for the 2018-2022 period. The data collection technique for this research uses secondary data originating from publications on the Indonesian Stock Exchange and uses documentation and bibliography methods, while the data analysis technique in this research is an analysis technique including statistical analysis and hypothesis testing. The research results state that Managerial Ownership and Institutional Ownership and the Independent Board of Commissioners partially or simultaneously have a negative effect on Company Value